A High FFP:PRBC Transfusion Ratio Decreases Mortality in All Massively Transfused Trauma Patients Regardless of Admission INR - Brown, Lisa M. (J Trauma, 2011)
BACKGROUND: Coagulopathy is present in 25-38% of trauma patients upon arrival to the hospital and these patients are four times more likely to die than trauma patients without coagulopathy. Recently, a high ratio of fresh frozen plasma (FFP) to packed red blood cells (PRBCs) has been shown to decrease mortality in massively transfused trauma patients. Therefore, we hypothesized that patients with elevated INR on arrival to the hospital may benefit more from transfusion with a high ratio of FFP:PRBC than those with a lower INR. METHODS: Retrospective multicenter cohort study of 437 massively transfused trauma patients. To determine if the effect of the ratio of FFP:PRBC on death at 24 hours is modified by a patient’s admission INR on arrival to the hospital we used contingency tables and logistic regression. RESULTS: Trauma patients who arrived to the hospital with an elevated INR had a greater risk of death than those with a lower INR. However, as the ratio of FFP:PRBC transfused increased, mortality decreased similarly between the INR quartiles. CONCLUSIONS: The mortality benefit from a high FFP:PRBC ratio is similar for all massively transfused trauma patients. This is contrary to the current belief that only coagulopathic trauma patients benefit from a high FFP:PRBC ratio. Furthermore, it is unnecessary to determine whether INR is elevated before transfusing a high FFP:PRBC ratio. Future studies are needed to determine the mechanism by which a high FFP:PRBC ratio decreases mortality in all massively transfused trauma patients.